Cardiovascular system is at higher risk of affecting by COVID-19: COVID-19 and CVD - Nejadghaderi, Seyed Aria; Heidari, Arash; Shakerian, Narges; Saghazadeh, Amene; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2020)
SARS-CoV-2 has shown its potential to cause severe manifestations among individuals with underlying cardiovascular disease (CVD). The patients infected with SARS-CoV-2 with pre-existing CVD are more likely to relapse. There are several reasons, including the prolonged hospitalization time as a consequence of their more severe illness and aberrant expression of angiotensin-converting enzyme 2 (ACE2) – the cell surface receptor of SARS-COV2 that is present on cardiac cells – and using drugs such as ACE inhibitors and angiotensin receptor blockers (ARBs) that alter the expression of ACE2. Besides, SARS-CoV-2 shares structural similarities with SARS-CoV-1, and that patients recovered from SARS-CoV1 have shown an increased risk of developing inflammatory, metabolic, and cardiac diseases. It makes some concerns that people who recovered from SARS-CoV2 are also liable to develop these chronic conditions later. Further studies should investigate the probability of recurrence of COVID-19 in patients with CVD and the development of approaches for the prevention of chronic inflammatory conditions in patients with CVD who recovered from COVID-19.